Current capabilities of prototyping technologies for multilayer printed circuit boards on a 3D printer - D. S. Vorunichev; K. Yu. Vorunicheva (Российский технологический журнал, 2021)
A new direction in 3D printing was investigated – prototyping of single-sided, double-sided and multilayer printed circuit boards. The current capabilities and limitations of 3D printed circuit board printing technology were identified. A comparative analysis of the characteristics of two desktop 3D printers presented in the industry for prototyping radio electronics, as well as the first professional machine DragonFly LDM 2020, which is a mini-factory for prototyping multilayer printed circuit boards, was carried out. The first practical experience of working and printing on DragonFly LDM 2020 supplied to the megalaboratory “3D prototyping and control of multilayer printed circuit boards” of the Institute of Radio Engineering and Telecommunication Systems MIREA – Russian Technological University is presented. The first samples of electronic boards printed on a 3D printer by the method of inkjet printing were obtained. An additive technology for the production of multilayer printed circuit boards is considered: printing with two printheads with conductive and dielectric nano-ink with two curing systems: an infrared sintering system for conductive ink and a UV curing system for dielectric ink. The LDM (Dragonfly Lights-out Digital Manufacturing) production method with the necessary maintenance is presented. The method allows the system to work roundthe-clock with minimal human intervention, significantly increasing the productivity of 3D printing and expanding the possibilities of prototyping. The materials used for 3D printing of multilayer printed circuit boards and their characteristics were investigated: dielectric acrylate nano-ink (Dielectric Ink 1092 – Dielectric UV Curable Acrylates Ink), conducting ink with silver nanoparticles (AgCite™ 90072 Silver Nanoparticle Conductive Ink). The research carried out allows us to compare the technological standards of printed electronics with traditional methods of manufacturing multilayer printed circuit boards for a number of parameters.